TROPIS: Tree Growth and Permanent Plot Information System - Vanclay, J.K. (1998)
TROPIS, the Tree Growth and Permanent Plot Information System, contains five elements: (1) a network of people willing to share permanent plot data and tree growth information, serviced by newsletters and information sources hosted at http:/'/www.cgnet.or g/cifor/research/tropis.htmI (or available from CIFOR), (2) an index of people and institutions holding permanent plot data, (3) a database management system to assist more efficient data management, (4) a system to facilitate site -matching by identifying comparable sites and allowing foreign data to be used when no local growth information exists, and (5) an inference system to allow growth estimates to be made in the absence of empirical data. The index or metadatabase contains references to 12,000 plots with 3,000 species provided by 100 contributors, and is growing at about 1,000 plots per month. Searches of the database are welcomed, and may be directed to the author.